Quick & easy Vietnamese cooking - Mingkwan, Chat (Singapore, 2007)
This is the perfect guide to exciting Vietnamese cooking. This book features 38 easy-to-prepare recipes like Fresh Salad Rolls with Chicken or Prawns, Grilled Lemongrass Beef Salad and Mango Coconut Tarts
Keywords: Cooking, Vietnamese; Cookbooks; Cuisine vietnamienne